2015
DOI: 10.1016/j.rbmo.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing luteinizing hormone supplementation timing strategies in older women undergoing ovarian stimulation

Abstract: In this open-label study, women aged 36-40 years undergoing ovarian stimulation were randomized to recombinant human FSH (rhFSH) plus recombinant human luteinizing hormone (rhLH) from stimulation day 1 (group A; n = 103), or rhFSH alone (days 1-5) followed by rhFSH plus rhLH from day 6 (group B; n = 99). The primary objective was equivalence in number of oocytes retrieved per patient. The mean (±SD) number of oocytes retrieved was 9.7 (±6.9) in group A and 10.9 (±6.5) in group B; the estimated difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Thirty-two full-text papers were assessed for eligibility. Twenty studies were excluded because they did not fulfill the inclusion criteria [ 44 63 ]. Overall, 12 RCTs were identified [ 9 , 20 , 36 , 37 , 64 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-two full-text papers were assessed for eligibility. Twenty studies were excluded because they did not fulfill the inclusion criteria [ 44 63 ]. Overall, 12 RCTs were identified [ 9 , 20 , 36 , 37 , 64 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several regimens have been proposed. Some authors suggested starting LH upon the onset of OS treatment [ 9 , 63 ], others starting from the intermediate phase of OS [ 36 , 37 ]. In the first phase of folliculogenesis, LH receptors are expressed predominantly in theca cells thereby promoting ovarian androgen production, which, as mentioned above, is reduced in advanced age women [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous studies, the number of oocytes retrieved was higher in the rFSH alfa arm than in the HP-hMG arm (22 ± 11.54 vs 15.1 ± 10.12) [ 14 , 79 ]. Interestingly, the PERSIST trial comparing a 2:1 formulation of rFSH alfa plus rLH (Pergoveris®) administered from Day 1 versus rFSH alfa (Gonal-F®) administered during Days 1–5 and supplemented with rLH from Day 6 of the stimulation cycle did not report a significant difference in terms of oocytes retrieved (9.7 vs 10.9, 95% confidence interval [CI]: − 3.15 to 0.59), therefore failing to meet its primary endpoint and yielding inconclusive evidence on the influence of rLH on oocyte yield [ 82 ].…”
Section: Clinical Differences Between Hcg and Lhmentioning
confidence: 99%
“…However, one month after ovarian autotransplantation, we observed trabecular bone formation containing osteoblasts border, channels and large gaps containing osteocytes ( Figure 6). As demonstrated by assisted reproduction, these follicles can be saved from degeneration and continue to grow and secrete sexual hormones 32 .…”
Section: Trabecular Bonementioning
confidence: 99%